The Influence of Adolescent Knowledge about Reproductive Health on the Intention to Avoid Smoking - Marmi Marmi; Sujono Riyadi (Indonesian Journal of Global Health Research, 2025)
Smoking is one of the leading causes of global mortality, significantly impacting reproductive health in both men and women. In Indonesia, the prevalence of adolescent smokers increased from 7.20% in 2013 to 9.10% in 2018, and it is projected to reach 16% by 2030 without effective interventions. The impact of smoking on reproductive health includes fertility disorders, reproductive cancer risks, and hormonal complications, which are often poorly understood by adolescents, particularly in areas with limited access to health information such as Sumenep, Madura.Objective: This study aims to analyze the relationship between adolescents' knowledge of the dangers of smoking to reproductive health and their intention to avoid smoking. Additionally, it seeks to provide scientific insights into the importance of reproductive health education as part of smoking prevention strategies.Methods: This cross-sectional study involved 200 adolescents aged 12–22 years, selected using proportional stratified random sampling. Data were collected through validated structured questionnaires, covering knowledge about the dangers of smoking and intentions to avoid smoking. Data analysis was performed using chi-square tests and logistic regression to identify relationships between variables.Results: The analysis revealed a significant relationship between adolescents' knowledge of the dangers of smoking to reproductive health and their intention to avoid smoking (p = 0.000). Adolescents with high levels of knowledge were more likely to have a strong intention to avoid smoking (OR = 3.25; 95% CI: 1.92–5.51). Pearson correlation analysis showed a positive relationship with an r-value of 0.373.Conclusion: Knowledge about the dangers of smoking to reproductive health plays a crucial role in shaping adolescents' intentions to avoid smoking. The findings of this study underscore the importance of comprehensive reproductive health education programs to increase adolescents' awareness and reduce smoking prevalence, especially in areas with limited access to health information.